Desain Mesin Penyegel Tutup Gelas Plastik untuk Minum Secara Semi Otomatis - Henry Vian Ivanda; Prantasi Harmi Tjahjanti; Iswanto Iswanto; Wiwik Sumarmi; Fuad Hamzah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The Cup Sealer machine, also known as a plastic cup sealing machine, is a device that seals plastic cups, preventing the contents from pouring into the glass. It also serves to keep liquids and things contained within them sanitary. This machine is frequently encountered operating on human power (manual). This study is a continuation of Community Service activities in the village of Sumbergedang Pasuruan. This machine design will be implemented in the village because the village has abundant clear/clear water that comes from Mount Penanggungan which has been processed into ready-to-drink water. The goal of this study is to create a plastic cup packaging machine that uses water from Mount Penanggungan in the village of Sumbergedang, Pasuruan, and then to improve the machine. The design uses SolidWork software with the input data being the cup sealer machine body component, the motor component for the sealing process, the cutter press component (plastic cutter when sealed), the ring component for the glass cup, and various extra components are used in the design. The results of the computation show that the design fits the requirements for moving forward with the production process.